Positive Pressure Ventilation - With Bag-Valve Mask Device Teaching Module - Thomas Nicholas; Brad Webb; Ben Boedeker (Association of American Medical Colleges, 2010)
Abstract This resource is a teaching module on positive pressure ventilation with a bag-valve mask device, constructed to help educate medical students, residents, and any other medical personnel interested in learning how to ventilate with a bag-valve mask. The module was developed by the Center for Advanced Airway Technology at the University of Nebraska Medical Center. The module contains video, photos, text, and audio narration demonstrating a stepwise approach to bag-valve mask ventilation. We are currently attempting to translate the document in order to increase the module's audience.